Producer's Role in Music Licensing For Short Movies - Esther Natasia Wongso; Annita Annita (Universitas Multimedia Nusantara, 2014)
The licensing process of copyrighted materials, especially songs and music for a film, is one of the responsibilities that a producer should fulfill, aside from other responsibilities like financing the film and managing all the needs of the cast and crew. However, the knowledge and awareness about copyright and music licensing are still very low in Indonesia. In this research, the writer will find out about the process of music licensing for a short movie. Through this research, we will look into the music licensing process for film, and national and international film festivals. Keywords: Producer, Music Licensing, Short Movie